ANALYSIS OF TUNED FILTERS FOR MITIGATION OF HARMONIC CURRENT DISTORTION OF RESIDENTIAL LOAD - Yogesh Bhujbal; Prof. P.N. Korde (International Journal of Innovations in Engineering Research and Technology, 2021)
Harmonics are the by-products of modern electronic devices that are nonlinearloads which create harmonics by drawing currentinrather than smooth sinusoidal manner. Any distribution circuit feeding nonlinear loads will contain some degree of harmonic frequencies. Due to the rapidly increasing number of non-linear loads in distribution systems, the harmonic distortion of the current and voltage increases.Non-linear loads are personal computer, television set (TV), fluorescent tube with electronic ballast, compact fluorescent lamp, battery charger, uninterrupted power supply (UPS) and any other equipment powered by switched-mode power supply (SMPS) unit. The harmonic distortion produced in residential buildings has not been given proper attention as linear loads were predominant earlier.